Comparison of Safety and Insurance Payments for Minor Hand Procedures Across Operative Settings - Billig, Jessica I. (JAMA Netw Open, 2020)
IMPORTANCE: Surgical procedures can be performed in different settings, but the association between the operative setting and patient safety and cost to the patient and payer is unknown. OBJECTIVE: To examine differences in complications, total payments, and out-of-pocket (OOP) spending for minor hand surgical procedures performed in office, ambulatory surgery center (ASC), and hospital outpatient department (HOPD) operative settings. DESIGN, SETTING, AND PARTICIPANTS: A retrospective, population-based cohort study was conducted using deidentified claims data from private employer-sponsored health insurance from January 1, 2009, to December 31, 2017. Patients aged 18 years or older undergoing carpal tunnel release, trigger finger release, excision of wrist ganglion, and excision of small hand masses (N = 468 365) were included. EXPOSURES: Operative setting, defined as procedures performed in the clinic setting, ASC, and HOPD. MAIN OUTCOMES AND MEASURES: Complications during the 90-day postoperative period, total payments (total facility and payer reimbursement), and OOP spending. RESULTS: Of the 468 365 patients, 296 378 women (63.3%) and 171 987 men (36.7%) underwent minor hand surgical procedures from 2009 to 2017, with 284 889 procedures (60.8%) performed in HOPDs, 158 659 procedures (33.9%) performed in ASCs, and 24 817 procedures (5.3%) performed in the office setting. Ninety-day complications occurred in 3.4% of procedures performed in HOPDs, 3.3% in ASCs, and 2.9% in office settings (P < .001). After controlling for patient characteristics, procedures performed outside of the office had higher odds of complications (HOPDs: odds ratio [OR], 1.32; 95% CI, 1.22-1.43; ASCs: OR, 1.24; 95% CI, 1.14-1.34). Compared with the office setting, procedures performed in HOPDs incurred an extra $1216 in total payments (95% CI, $1184-$1248) and $115 in OOP expenses (95% CI, $109-$121). Procedures performed in ASCs cost an additional $709 (95% CI, $676-$741) and $140 in OOP expenses (95% CI, $134-$146). Transitioning ASC and HOPD procedures to the office setting could have saved an estimated $6 million annually in OOP expenses during the study period. CONCLUSIONS AND RELEVANCE: The findings of this study suggest that minor hand surgery performed in the office setting is safe and less costly compared with ambulatory and hospital-based operations. Shifting minor surgical procedures to the office setting may lead to substantial cost savings for payers and patients without compromising care quality.